Four Mining Greats To Be Inducted Into The National Mining Hall Of Fame (Society for Mining, Metallurgy & Exploration, 2011)
The National Mining Hall of Fame and Museum (NMHFM) in Leadville, CO will induct the class of 2011 on Sept. 10, 2011. Representing the coal, metallurgical/processing, research and development, marble and lead industries, this year?s inductees cover a diverse crosssection of the mining industry. William Francis Diamond, Wayne Hazen, Redfield Proctor and Jeffrey Zelms will join 210 other mining industry pioneers when they are formally inducted into the National Mining Hall of Fame at the 24th Annual Induction Banquet and Ceremony. The members of this year?s class were selected for being visionaries, leaders and ambassadors both within their own sectors and across the industry at large. Diamond had an illustrious engineering and managerial career that spanned four decades with Island Creek Coal Co. During that time, he was responsible for the engineering and construction of the deepest coal mines producing in North America at the time.